2019
DOI: 10.3389/fonc.2019.00095
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Concentration of Circulating Cell-Free DNA in Breast Cancer: A Meta-Analysis

Abstract: The diagnostic value of the concentration of circulating cell-free DNA (cfDNA) for breast cancer has generated inconsistent results. The aim of this study was to evaluate the first diagnostic value of the concentration of cfDNA for breast cancer by meta-analysis. Studies were retrieved by searching PubMed, Cochrane Library, and Web of Science before June 2018. Sensitivity, specificity, diagnostic odds ratio (DOR), the summary receiver operating characteristic (SROC) curve, and the area under curve (AUC) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 35 publications
1
27
1
Order By: Relevance
“…[56][57][58] cfDNA, as a liquid-based diagnostic tool, possessed equal sensitivity and specificity of 87% for breast cancer. 59 A meta-analysis further indicated that the plasma might be a good source of cfDNA for detection of breast cancer. 59 In a patient with HER2-positive BCBM, Siravegna et al 60 reported that cfDNA was more informative and sensitive than radiologic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] cfDNA, as a liquid-based diagnostic tool, possessed equal sensitivity and specificity of 87% for breast cancer. 59 A meta-analysis further indicated that the plasma might be a good source of cfDNA for detection of breast cancer. 59 In a patient with HER2-positive BCBM, Siravegna et al 60 reported that cfDNA was more informative and sensitive than radiologic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…There are several important consequences of "oncogenic drivers" in benign conditions. First, there are the implications for early detection of cancer based on sensitive blood tests that assess circulating cell-free DNA (cfDNA) [130][131][132]. If mutations identical to those found in cancer also occur in conditions with no malignant predisposition, their presence may confound the early diagnosis of cancer premise that is the basis of these blood-based screening tests, such as the multicancer detection blood test developed by GRAIL that has been granted breakthrough status by the US Food and Drug Administration [133].…”
Section: Adrenocortical Cancersmentioning
confidence: 99%
“…However, since the tumor is a "moving target", with significant molecular alterations evolving during progression and in response to therapeutics, extending liquid biopsy to the genetic analysis of CTCs will further help to inform on these two relevant aspects of carcinogenesis and, consequently, to reduce mortality. In addition to CTCs, tumors can release DNA into the bloodstream, which is described as circulating tumor DNA (ctDNA) [13]. This cell-free DNA (cfDNA), although present also in healthy individuals, is significantly increased in cancer subjects [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ctDNA is recognized as a novel biomarker in the diagnosis of several cancers, including gastric cancer, non-small lung cancer, and hepatocellular carcinoma [15][16][17]. In BC, the concentration of ctDNA has potential first diagnostic value for BC [13,18]. Given that the combination of as many parameters as possible may lead to achieve the maximum level of diagnostic and/or prognostic accuracy, in the present study, we carried out liquid biopsy through CTCs enumeration, ctcDNA and cftDNA quantification and sequencing, in early BC patients before and after surgery ( Figure 1), providing, for the first time to our knowledge, a complete picture, even though still limited to a small cohort of patients, of this potentially important diagnostic and prognostic strategy.…”
Section: Introductionmentioning
confidence: 99%